Pemberdayaan Santri Melalui Literasi Digital Marketing di Pondok Pesantren Al-Muqriyah - M.arif Fadilah; Raihan Syafi Ramadhan; M. faiz pratama (CV. ITTC INDONESIA, 2026)
This community service aims to empower the santri of Pondok Pesantren Al-Muqriyah through digital marketing literacy, considering the importance of digital skills in the globalization era to enhance economic independence and the relevance of traditional Islamic education. The topic was chosen because santri often lack skills in online marketing, which can open entrepreneurial opportunities. The service methods include interactive workshops, practical training, and pre-post evaluations through surveys. Results show a significant increase in the santri's digital competencies, such as social media management and e-commerce strategies, as well as improved self-confidence. This conclusion underscores the importance of integrating digital technology in pesantren to support sustainable development in rural communities